Spontaneous tumour lysis syndrome associated with contrast dye iohexol use in mantle cell lymphoma. (15th July 2014) - Yun, Seongseok; Vincelette, Nicole D; Phan, Tuan; Anwer, Faiz
Abstract : We describe a case of a 73-year-old man who presented with right-sided abdominal pain associated with palpable mass. Initial laboratory examination was normal except lactate dehydrogenase level. Subsequent CT image showed situs inversus and splenic mass with multiple lymph nodes enlargement. Biopsy taken from the splenic mass demonstrated mantle cell lymphoma. Staging CT examination was performed with intravenous contrast, and patient developed altered mental status, respiratory failure and acute kidney injury requiring intensive care unit care. Laboratory examination revealed hyperuricaemia, hyperphosphataemia, hyperkalaemia and hypocalcaemia, which are consistent with spontaneous tumour lysis syndrome. The patient was successfully treated with rasburicase and haemodialysis, and completed the first course of chemotherapy without further complications.